Matter and consciousness : a contemporary introduction to the philosophy of mind - Churchland, Paul M. (A Bradford book, 1999)
The ontological problem (the mind-body problem) Dualism Philosophical behaviorism Reductive materialism (the identity theory) Functionalism Eliminative materialism The semantical problem Definition by Inner Ostension Philosophical behaviorism The theoretical network thesis and folk psychology Intentionality and the propositional attitudes The epistemological problem The problem of other minds The problem of self-conscious Methodological problem Idealism and phenomenology Methodological behaviorism The cognitive/computational approach Methodological materialism Artificial intelligence Computers: Some elementary concepts Programming intelligence: The piecemeal approach Neuroscience Neuroanatomy: The evolutionary background Neurophysiology and neural organization Neuropsychology Cognitive neurobiology AI again: Parallel distributed processing Expanding our perspective 1. The distribution of intelligence in the universe 2. The expansion of introspective consciousness